CARING TO BE FORGOTTEN: AN OVERVIEW OF FAMILY RESILIENCE IN ELDERLY DEMENTIA CAREGIVERS - Widhi Winantu, Dyah; Ganes Widayanti, Costrie (HEARTY, 2025)
Indonesia is entering the aging population period, characterized by an increase in life expectancy and the growing number of elderly individuals. One of the prevalent health issues among the elderly is dementia, which imposes a significant stress burden on caregivers. This study aims to explore family resilience in caregivers of elderly individuals with dementia. A qualitative approach using a case study method was employed. Subjects were selected through purposive sampling, data validity was ensured through source triangulation, and data were analyzed using content analysis. The findings reveal that both families exhibited similar resilience dynamics, characterized by a belief system emphasizing a positive perspective on the situation and reliance on faith in God. Organizational patterns displayed flexibility and the provision of support. The family dynamics of Subject EM were more flexible compared to Subject NR, while the support received by both subjects played a critical role in fostering family resilience. Communication processes were stronger in Subject EM’s family compared to Subject NR’s, yet communication in both families contributed to the overall resilience dynamics. In conclusion, this study indicates that family resilience is established through a belief system, organizational flexibility, support, and effective communication.